Path planning aware of soil compaction for steep slope vineyards - Santos, Lus; Ferraz, Nuno; Neves dos Santos, Filipe; Mendes, Jorge; Morais, Raul; Costa, Pedro; Reis, Ricardo (2018 IEEE International Conference on Autonomous Robot Systems and Competitions (ICARSC), 2018)
The intensive use of agricultural machinery is promoting the soil compaction. The use of agricultural robots or autonomous machinery can intensify this problem, due its capacity to replicate the same trajectories. One of the possible strategies to minimize the effects of soil compaction is to control agricultural traffic instead of common random traffic. Since geo-referencing systems are present in almost all field operations it is possible to optimize trajectories to avoid to damage the crop and intensify the soil compaction. The controlled agricultural traffic on farms will not only increase production capacity, the incomes as well as the quality of the soil. In this work a novel approach based on A-star algorithm is proposed to reduce soil compaction in steep slope vineyards.